TITLE: DISASTER RISK REDUCTION (DRR) MEASURES FOR HERITAGE SITE AT RISK, A CASE OF BAHU DERE IN SWABI-KHYBER PAKHTUNKHWA, PAKISTAN - Ar. Mir Wali Shah; Ar. Iftikhar Ali; Ar. Qasim Ali Shah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
Background: The assets of previous civilizations, known as cultural heritage, are at risk from both natural and man-made disasters. It is extremely risky to lose these assets, whether they are tangible or intangible, due to existing hazards and vulnerabilities. Purpose: This study will concentrate on strategies for reducing disaster risk for cultural heritage sites that are at risk from natural or man-made disasters. Cultural heritage is vulnerable to a wide range of risks, including earthquakes, torrential downpours, urbanization, development, tourism, floods, vandalism, thefts, winds, sliding, and other dangers depending on where the site is located. Methods: This article will use cultural heritage sites as an example, using a practical survey to elaborate on risk assessments for these sites. It will also use several modules to research and suggest disaster risk reduction strategies for these sites using real-world examples and case studies. Results and Conclusions: This study will offer recommendations for heritage sites including how to reduce disaster risk, the function of stakeholders, and the ability of the community to protect the legacy that is vulnerable to disasters. Each heritage site that faces a different hazards can use a module. Implication: This study has a significant impact on preserving cultural heritage sites that are in danger and require evaluations through standardized modules for heritage sites in a community and region. To protect the lifelines of civilizations in danger, a set of straightforward principles is offered with a case study of a cultural site.